St Andrew's COVID-19 Surgery Safety (StACS) study: Skin cancer. Issue 5 (1st October 2021) - Miranda, B. H.; Jica, R. C. I.; Pinto-Lopes, R.; Mopuri, N.; Sood, M. K.; Tare, M.; Shelley, O.; El-Muttardi, N.; ,; Ahmad, Fateh; Banwell, Miles E; Barnes, David E; et al.
Abstract: Background: Skin cancer represents the most common malignancy worldwide and it is imperative that we develop strategies to ensure safe and sustained delivery of cancer care which are resilient to the ongoing impact of COVID-19. Objective: This study prospectively evaluates the COVID-19 related patient risk and skin cancer management at a single tertiary referral centre, which rapidly implemented national COVID-19 safety guidelines. Method: A prospective cohort study was performed in all patients who underwent surgery for elective skin cancer service management, during the UK COVID-19 pandemic peak (April–May 2020). 'Real-time' 30-day hospital database deceased data were collected. Random selection was undertaken for patients who either underwent operative (surgery group) management or remained on the waiting list (control group); these groups were also prospectively followed-up within a controlled cohort study design and telephoned at the end of June 2020 for the control group or 30 days post-operatively. Results: Of the 767 patients who had operations, there were no COVID-19 related deaths. Both the surgery ( n  = 384) and control ( n  = 100) groups were matched for age, sex, ethnicity, BMI, presence of comorbidities, smoking and positive COVID-19 contact. There were no differences in post-operative versus any symptom development (1.3%, 5/384 vs. 4%, 4/100, p  = 0.093), or proportion of positive tests (8.6%, 33/384 vs. 8%, 8/100; p  = 0.849), between the surgery and control groups. Conclusion: These data support continued and safe service provision, and no increased risk to skin cancer patients who require surgical management, which is vital for continuation of cancer treatment in the context of a pandemic. Level of Evidence: II.